Aerobic exercise 3 times per week in adult rats did not influence the progression of periodontal disease - Souza, Thalita Borges; Baptista, Rafael Reimann (Frontiers in Sports and Active Living, 2023)
Physical exercise has proven efficacy in the prevention and treatment of chronic diseases, and its antiinflammatory effect has been evaluated as a potential preventive factor in the progression of periodontal disease, in addition to improving physiological parameters. To test this hypothesis regarding its preventive factor, we evaluated the effects of aerobic training on the progression of periodontal disease in 8-month-old Wistar rats (n=44). The animals underwent a swimming protocol lasting six weeks, with periodontal disease induced by ligature in the fifth week, totaling fourteen days of ligature placement. Anthropometric parameters were measured for subsequent calculations of BMI and Lee's Index. Interleukin-1β testing was performed to measure serum inflammatory parameters, and alveolar bone loss was measured using images to calculate the area of loss. The trained animals showed no significant differences compared to the non-trained animals in terms of anthropometric measures. Regarding the area of bone loss, although there were significant differences between the groups with and without periodontal disease, exercise did not demonstrate an impact on rats with the disease. IL-1β analysis did not detect any measurable values in the samples in either group. These findings indicate that the applied exercise protocol was not sufficient to attenuate the progression of periodontal disease. This study did not find an effective impact of physical exercise on the analyzed parameters; however, the results are important in highlighting that the experimental animal model for inducing periodontal disease is efficient, which may encourage further investigations to determine factors that can attenuate its progression. Similarly, the application or development of new exercise protocols that can benefit and enrich the discussion on its positive effects in this disease is important, as there is already evidence suggesting an effective relationship between exercise and disease progression.